Expressão de genes associados à restrição hídrica em sementes de Physalis angulata L. (SOLANACEAE) - Marques, Alexandre Correia Silva de Santana (2012)
Physalis angulata have been studied due to its medicinal properties conferred by poly-oxygenated metabolites and vitaesteroids, mainly physalins, showing immunomodulatory, antimicrobial and anticancer activities. The recent demand for P. angulata requires better understanding the plant physiological characteristics to promote its agricultural development. One focus is the development of varieties resistant to water restriction, being the main productivity limiting factor in brazilian northeast semi-arid. This work aims to establish protocols for optimization of germination under water deprivation through osmopriming technique and identify genes that may assist tolerance to water deficit in P. angulata. Thus, was quantified gene expression in seeds of P. angulata previously osmoprimed and then subjected to water restriction. Osmopriming can be used as a pre-germinative treatment as it increased germination percentage and rate when transferred to distilled water after water deprivation stress. The HSP17, HSP18, TPX and APX gene expression were induced in seeds subjected to water deficit. Primed seeds then submitted to water restriction maintained elevated expression of the genes TPRP-F1 and APX higher than unprimed seeds. The relative expression of these genes in P. angulata allowed associate them to the water restriction and its tolerance, which can be used as a marker to develop new genotypes better adapted to drought conditions in P. angulata and possibly other species.